The historical analysis of childhood and juvenile delinquency: Implications of american social trend and thought. (16th September 2022) - Allen, Terrence T.
Abstract: This paper provides a comprehensive historical analysis of policies, theories and approaches to juvenile delinquency. It also examines the deficits and advantages of the application of adult based criminological theory as a means of explaining, and irradiating juvenile crime. Additionally, the author explores the dynamics of the definition of childhood, the pervasiveness of the mistreatment of children, and how these ever‐evolving conditions have impacted juvenile justice policy. Moreover, the paper dissects classical, positivist, and neo‐classical criminological theories efforts to explain society's response to juvenile crime. In the conclusion, the author draws implications to contemporary approaches to the treatment of juvenile delinquency based in the positivist school of thought. Finally, the author discuss the significance of understanding the historical implications for policymakers and practitioners.